First detection of Ehrlichia chaffeensis, Ehrlichia canis, and Anaplasma ovis in Rhipicephalus bursa ticks collected from sheep, Turkey - AKYILDIZ, GÜRKAN (My University, 2024)
Anaplasmosis and ehrlichiosis are important tick-borne rickettsial diseases of medical and veterinary importance that cause economic losses in livestock. In this study, the prevalence of Anaplasma ovis, Ehrlichia canis and Ehrlichia chaffeensis was investigated in ticks collected from sheep in various farms in Van province, which is located in the Eastern Anatolian Region of Turkey. The ticks used in this study were collected by random sampling in 26 family farm business in 13 districts of Van province. A total of 688 ticks were collected from 88 sheep and 88 tick pools were created. All ticks identified morphologically as Rhipicephalus bursa. Phylogenetic analysis of Chaperonin and 16S rRNA gene sequences confirmed A. ovis, E. canis and E. chaffeensis in this study. Of the 88 tick pools tested, 28.41% (25/88) were positive for at least one pathogen. Anaplasma DNA was detected in five of the 88 pools (5.68%), E. canis DNA was detected in 19 of the 88 pools (21.59%), and E. chaffeensis DNA was detected in one of the 88 pools (1.14%) of R. bursa ticks. To our knowledge, this is the first report describing the presence of A. ovis, E. canis, and E. chaffeensis in R. bursa ticks collected from sheep in Turkey. Further studies are needed to investigate other co-infections in sheep in Turkey.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Sheep; tick-borne parasitic diseases; Turkey